2016
DOI: 10.1182/blood.v128.22.3330.3330
|View full text |Cite
|
Sign up to set email alerts
|

Selinexor Shows Synergy in Combination with Pomalidomide and Low Dose Dexamethasone in Patients with Relapsed / Refractory Multiple Myeloma

Abstract: Introduction - The nuclear export protein exportin 1, (XPO1) is overexpressed in a wide variety of cancers including multiple myeloma (MM). Selinexor is a first-in-class Selective Inhibitor of Nuclear Export (SINE) compound that binds and inactivates XPO1. Selinexor forces nuclear retention and reactivation of tumor suppressor proteins (TSPs; NF-kB, p53 and FOXO) and reduction of many proto-oncogenes, including MDM2, MYC and Cyclin D. In murine MM models, the combination of selinexor with IMIDs shows synergist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The preliminary results of the combination arm of selinexordexamethasone with pomalidomide in patients previously treated with lenalidomide and ! 1 PI (another arm of the phase Ib/II STOMP trial) were reported by Chen et al 83 Selinexor was dose escalated, starting QW at 80 mg or BIW at 60 mg, with all patients receiving pomalidomide (4 mg/d orally for days 1-21) and dexamethasone (40 mg QW in a 28-day cycle). Eleven patients were enrolled at the time of reporting, including five with MM refractory to both lenalidomide and bortezomib.…”
Section: Sine Compounds Plus Imidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preliminary results of the combination arm of selinexordexamethasone with pomalidomide in patients previously treated with lenalidomide and ! 1 PI (another arm of the phase Ib/II STOMP trial) were reported by Chen et al 83 Selinexor was dose escalated, starting QW at 80 mg or BIW at 60 mg, with all patients receiving pomalidomide (4 mg/d orally for days 1-21) and dexamethasone (40 mg QW in a 28-day cycle). Eleven patients were enrolled at the time of reporting, including five with MM refractory to both lenalidomide and bortezomib.…”
Section: Sine Compounds Plus Imidsmentioning
confidence: 99%
“…Also, the constitutional and gastrointestinal side effects appear to be reduced when selinexor is given QW (as opposed to BIW) in combination with other anti-MM drugs. 83,85 Eltanexor, the second-generation SINE compound, has demonstrated a broad therapeutic window with reduced penetration of the bloodebrain barrier across species (mouse, rat, monkey) compared with selinexor. 51 After oral administration, animals treated with eltanexor showed a lower percentage of body weight loss and improved food consumption than animals similarly treated with selinexor.…”
Section: Constitutional/gastrointestinalmentioning
confidence: 99%
“…The all-oral combination of selinexor, a first-in-class selective inhibitor of nuclear export, with POMd has demonstrated in a phase 1/2 trial 61 a 60% ORR. Responses were rapid in onset, and 10% CR was achieved.…”
Section: Design and Characteristicsmentioning
confidence: 99%
“…Pomalidomide, an oral immunomodulatory agent, has demonstrated antimyeloma activity in the context of lenalidomide resistance and is the only agent that has been extensively studied in patients previously treated with lenalidomide, including those who received pomalidomide immediately after lenalidomide 14‐17 . Pomalidomide has also demonstrated antimyeloma activity synergistic with multiple agents, supporting its integration into novel triplet regimens 16,18‐23 . The combination of pomalidomide, bortezomib, and dexamethasone (PVd) was approved in the European Union and other countries on the basis of the findings of the registrational phase 3 OPTIMISMM study in lenalidomide‐pretreated patients (70% with lenalidomide‐refractory disease) with relapsed or refractory MM (RRMM) in early lines of therapy (median of two prior lines of therapy) 17,24,25 .…”
Section: Introductionmentioning
confidence: 99%